Modelación física de la capacidad portante de cimentaciones superficiales considerando el efecto del clima. (2019)
In recent years, different ways to quantify the bearing capacity of soils have been studied, but there is no solid theory that considers all the variables that influence soil shear resistance, including the effect of partial saturation. During the last decade, the classical theory of Terzaghi (1945) has continued to be used for saturated soils, where the maximum soil capacity can be evaluated. To include the effect of partial saturation, theoretical formulations have been developed for partially saturated soils such as Bishop's (1959), where the air-water interface is evaluated. More recent approaches such as those of Costa, Cintra, & Zornberg (2003), S. Y. Oloo, Fredlund, & Gan (1997), Vanapalli & Mohamed (2007), include suction to describe shear resistance. In the present document, a theoretical review of the existing formulations to evaluate the bearing capacity of partially saturated soils is presented initially, as well as of the available methods to evaluate the suction and the parameters of shear resistance in condition of partial saturation. Subsequently, physical modeling of the bearing capacity of a shallow foundation in Bogotá soil, for different degrees of saturation, was performed. The above to relate the results of these tests on a reduced scale with the parameters of shear resistance (cohesion and internal friction angle) obtained by direct shear tests on the natural soft soil. The moisture contents used in the models were 49%, 27%, and 23%. Finally, the same procedure was used with reconstituted samples of the same soil where physical models were made for compacted samples and with different moisture contents (34%, 28%, and 24%). The soil used was characterized according to INVIAS 2013 specifications and experimental procedures proposed by Oh & Vanapalli (2013) and Sáez & Escario (1986) were used to evaluate the resistance parameters in natural soils. It was found that the change in moisture directly influences the shear strength, increasing soil suction and bearing capacity up to 1000%.